TI_GERICHTE 11.2010.82 vom 28. Februar 2012 , Misure cautelari in una causa di divorzio: contributo alimentare per la moglie - TI Tribunale d'appello (2012)
Misure cautelari in una causa di divorzio: contributo alimentare per la moglie